I am number four the lost files : hidden enemy - Lore, Pittacus; Lore, Pittacus; Lore, Pittacus; Lore, Pittacus (New York Harper, an imprint of HarperCollinsPublishers, 2014)
Collects three novellas that fill in missing parts of the Lorien story, including Five's early years on Earth and Mark James' trials after the Mog attack on Ohio
Five's legacy -- Return to paradise -- Five's betrayal
1
Keywords: Extraterrestrial beings -- Juvenile fiction; Extraterrestrial beings; Science fiction -- Juvenile literature; Science fiction; Extraterrestrial beings -- Fiction; Science fiction; Fiction; Juvenile works